Effectiveness of Community Based Group Therapy for Chronic Low Back Pain in Older Women in Bangladesh: A Randomised Controlled Trial - Akhter, Tanzila; Bhuiyan, Saruar Hossain; Hossain, Zahid; Hossain, Tofajjal; Khan, Abid Hasan; Kabir, Feroz; Sultana, Kumkum; Jahan, Sharmila (Journal of Health Science and Medical Research, 2025)
Objective: Group therapy involves multiple people being treated by one or more health professionals. It can cure physical and psychological conditions; such as attention-deficit/hyperactivity disorder (ADHD), emotional trauma, anxiety, despair, and post-traumatic stress disorder (PTSD). This study investigates whether community-based group therapy helps older women with chronic low back pain. Material and Methods: The study was a randomized controlled trial, with 40 patients divided into control and intervention groups. The control group received conventional treatment in an institute-based rehabilitation (IBR) facility, while the intervention group received the same exercise program in a community-based rehabilitation (CBR) setting. Both groups received supervised 30-minute sessions five days a week for eight weeks. The numeric pain rating scale (NPRS) was used to measure the severity of pain and the Roland-Morris Disability Questionnaire (RMDQ) measured physical disability due to low back pain in older women. Results: The average age of the participants was 56 (53 to 58.50). The BMI findings were 7.5% (n=3) of participants being underweight and 45% (n=18) of participants being overweight. In terms of pain and physical disability due to low back pain, the CBR group showed significant improvement (p-value<0.05) in cases of both inter- and intra-group comparison using the IBR treatment facility. Conclusion: Group therapy treatment reduces low back pain and prevents the severity of back pain in older women, thereby improving their quality of life. This study shows that group-based physical therapy helps relieve chronic low back pain. Strengthening, stretching, and flexion exercises in groups improve quality of life and minimise discomfort.